Le complexe monumental suburbain et l’ensemble funéraire de Saint-Martin-au-Val (Chartres, Eure-et-Loir) : état de la recherche (2006-2011) - Bruno Bazin; Emmanuel Bouilly; Vincent Drost; Isabelle Godin; Stéphane Hérouin; Christophe Loiseau; Apolline Louis; Stéphanie Raux; Julie Rivière; Jonathan Simon; Stéphane Willerval (Gallia)
Since 2006, the remains of a possible Gallo-Roman cult complex of over 6 ha, located in a suburban area of Autricum (ancient Chartres), have been excavated not far from the centre of Chartres. The analysis of the masonry structures revealed a quadriporticus with corner pavilions surrounding a courtyard of over 4.5 ha. The temple has not been located but could have been partly incorporated into the west portico. The current archaeological research related to the north-east corner of the quadriporticus. The main masonry structures left, most of them foundations, were built between 70 and 120 AD. Ca. AD 120-130, the construction of rectangular, apsidal exedrae is attested on the eastern facade. Between the middle and the second half of the 2nd c. AD, construction work seemed to have been interrupted; at least there is no indication that work was resumed and from the early 3rd c. AD the monument became an open quarry. Traces of its demolition are visible through the presence of reused masonry, debris, the remains of workshops producing copper alloys and those of lime kilns. Ca. AD 270-280, east of the north-east corner pavilion, more than one hundred bodies were buried in a large pit about 50 meters long. The ongoing study shows that this makeshift disposal in a remote part of the city was the result of an epidemic. The site was definitively abandoned towards the end of the 4th c. AD when lime production ceased.